Step
*
of Lemma
bag-summation-append
∀[R:Type]. ∀[add:R ⟶ R ⟶ R]. ∀[zero:R].
  ∀[T:Type]. ∀[f:T ⟶ R]. ∀[b,c:bag(T)].  (Σ(x∈b + c). f[x] = (Σ(x∈b). f[x] add Σ(x∈c). f[x]) ∈ R) 
  supposing IsMonoid(R;add;zero) ∧ Comm(R;add)
BY
{ (Auto THEN (BagD (-2) THENA Auto) THEN (Subst' as = bs ∈ bag(T) 0 THENA Auto) THEN Thin (-1)⋅ THEN ThinVar `as') }
1
1. R : Type
2. add : R ⟶ R ⟶ R
3. zero : R
4. IsMonoid(R;add;zero)
5. Comm(R;add)
6. T : Type
7. f : T ⟶ R
8. c : bag(T)
9. bs : T List
⊢ Σ(x∈bs + c). f[x] = (Σ(x∈bs). f[x] add Σ(x∈c). f[x]) ∈ R
Latex:
Latex:
\mforall{}[R:Type].  \mforall{}[add:R  {}\mrightarrow{}  R  {}\mrightarrow{}  R].  \mforall{}[zero:R].
    \mforall{}[T:Type].  \mforall{}[f:T  {}\mrightarrow{}  R].  \mforall{}[b,c:bag(T)].    (\mSigma{}(x\mmember{}b  +  c).  f[x]  =  (\mSigma{}(x\mmember{}b).  f[x]  add  \mSigma{}(x\mmember{}c).  f[x])) 
    supposing  IsMonoid(R;add;zero)  \mwedge{}  Comm(R;add)
By
Latex:
(Auto
  THEN  (BagD  (-2)  THENA  Auto)
  THEN  (Subst'  as  =  bs  0  THENA  Auto)
  THEN  Thin  (-1)\mcdot{}
  THEN  ThinVar  `as')
Home
Index